Metabolite profile in hereditary spastic paraplegia analyzed using magnetic resonance spectroscopy: a cross-sectional analysis in a longitudinal study - Montanaro, Domenico; Vavla, Marinela; Frijia, Francesca; Coi, Alessio; Baratto, Alessandra; Pasquariello, Rosa; Stefan, Cristina; Martinuzzi, Andrea (Frontiers in Neuroscience, 2024)
Background Hereditary Spastic Paraplegias (HSP) are genetic neurodegenerative disorders affecting the corticospinal tract. No established neuroimaging biomarker is associated with this condition. Methods A total of 46 patients affected by HSP, genetically and clinically evaluated and tested with SPRS scores, and 46 healthy controls (HC) matched by age and gender underwent a single-voxel Magnetic Resonance Spectroscopy sampling (MRS) of bilateral pre-central and pre-frontal regions. MRS data were analyzed cross-sectionally (at T0 and T1) and longitudinally (T0 vs. T1). Results Statistically significant data showed that T0 mI/Cr in the pre-central areas of HSP patients was higher than in HC. In the left (L) pre-central area, NAA/Cr was significantly lower in HSP than in HC. In the right (R) pre-frontal area, NAA/Cr was significantly lower in HSP patients than in HC. HSP SPG4 subjects had significantly lower Cho/Cr concentrations in the L pre-central area compared to HC. Among the HSP subjects, non-SPG4 patients had significantly higher mI/Cr in the L pre-central area compared to SPG4 patients. In the R pre-frontal area, NAA/Cr was reduced, and ml/Cr was higher in non-SPG4 patients compared to SPG4 patients. Comparing “pure” and “complex” forms, NAA/Cr was higher in pHSP than in cHSP in the R pre-central and R pre-frontal areas. The longitudinal analysis, which involved fewer patients (n = 30), showed an increase in mI/Cr concentration in the L pre-frontal area among HSP subjects with respect to baseline. The patients had significantly higher SPRS scores at follow-up, with a significant positive correlation between SPRS scores and mI/Cr in the L pre-central area, while in bilateral pre-frontal areas, lower SPRS scores corresponded to higher NAA/Cr concentrations. To explore the discriminating power of MRS in correctly identifying HSP and controls, an inference tree methodology classified HSP subjects and controls with an overall accuracy of 73.9%, a sensitivity of 87.0%, and a specificity of 60.9%. Conclusion This pilot study indicates that brain MRS is a valuable approach that could potentially serve as an objective biomarker in HSP.